Development of a Collaborative Leadership Model in Conflict Management in Secondary Schools: A Systematic Literature Review and Its Implications for Vocational and Senior High Schools in West Sumatra - Sunarti Al Mondar; Azizah Dwi Sa’diyah; Nurizrah Gistituati; Rusdinal; Nellitawati; Anisah; Merika Setiawan; Irsyad (International Journal of Science and Environment (IJSE), 2026)
Conflicts in senior high schools (SMA) and vocational high schools (SMK) in West Sumatra often arise from differences in academic policies and organizational pressures, but the lack of a specific collaborative leadership model is a major research gap. This study aims to develop a conceptual model of collaborative leadership in conflict management. Using a systematic literature review (SLR) with the PRISMA protocol, the population included publications from 2015–2025 in Scopus, Google Scholar, and national journals; the sample was purposively selected based on relevance to Indonesian secondary schools. The search protocol, using keywords such as "collaborative leadership" and "conflict management," was analyzed through thematic synthesis and content analysis. The results identified a five-dimensional model: collaborative leadership, principal competency, conflict process, supportive culture, and organizational impact. The conclusions confirm that this model fills a local gap with implications for principal training and education policy in West Sumatra.